Education for Innovation (E4I): Exploring the Developmental Process of a Canadian Curriculum Resource - Jarvis, Daniel; Black, Glenda L.; Cantalini-Williams, Maria T. (Alberta Journal of Educational Research, 2020)
The Rideau Hall Foundation (RHF) in Ottawa, Canada selected the Schulich School of Education (SSoE) at Nipissing University to create educational resources to correspond with the release of two 2017 publications (Innovation Nation written for emergent readers; and Ingenious written for older readers. Both books were co-authored by The Right Honourable David Johnston (former Governor General of Canada) and Tom Jenkins as part of the Canada 150 sesquicentennial celebrations. The SSoE organized school teacher writing teams in summer 2017 and produced three cross-curricular Education for Innovation (E4I) resources (Early Learning; Grades 1-8; Grades 7-12) each of which included an Innovation Cycle model, sample key innovation learning experiences, and suggestions for culminating Innovation Celebrations. Teacher candidates from participating SSoE faculty classes also created curriculum-specific Innovation units which were subsequently revised by teacher teams and then implemented and reviewed by teachers from different educational contexts (e.g., public schools, private schools, homeschools). The E4I project collaboration involved university faculty, teachers, teacher candidates, and community partners. Based on participant survey data, researchers identified reported benefits and challenges relating to the overall developmental process. Findings indicate that the experiences of inquiring, ideating, incubating, and implementing the E4I resources closely reflected the phases found within the Innovation Cycle model. Feedback from teachers confirmed the usefulness of E4I for promoting innovation skills and mindsets in their students. Further themes emerging from the process survey data analysis include the evidence of, and need for: solid leadership, flexible support, iterative mindsets, and organic organizational structures. Key words: Innovation, Education, Curriculum, Interdisciplinary La Fondation Rideau Hall (FRH) à Ottawa, Canada, a sélectionné la Schulich School of Education (SSoE) de l’Université Nipissing pour élaborer des ressources didactiques dans le cadre de la publication de deux livres en 2017, Innovation Nation pour lecteurs débutants et Ingenious pour lecteurs plus âgés. Les deux livres ont été rédigés par le très honorable David Johnston, ancien Gouverneur général du Canada, en collaboration avec Tom Jenkins dans le cadre des célébrations du cent-cinquantenaire du Canada. La SSoE a organisé des équipes de rédaction pour enseignants à l’été 2017 et a produit trois ressources multidisciplinaires portant sur l’éducation pour l’innovation (E41), chacune comportant un modèle du cycle d’innovation, un échantillon des expériences d’apprentissage axées sur l’innovation et des suggestions axées sur les célébrations de l’innovation comme activité culminante. Des stagiaires suivant des cours avec l’équipe professorale de SSoE ont également créé des unités portant sur l’innovation alignées avec les programmes d’études. Par la suite, des équipes d’enseignants ont révisé les unités et des enseignants de divers contextes éducationnels (par exemple, écoles publiques, écoles privées, enseignement à domicile) les ont mises en œuvre et les ont commentées. Le projet E41 a impliqué la collaboration du personnel enseignant de l’université, d’enseignants, de stagiaires et de partenaires communautaires. À partir des données de sondages, les chercheurs ont identifié les avantages et les défis de l’ensemble du processus de développement. Les résultats indiquent que les expériences consistant à poser des questions, à imaginer, à réfléchir et à mettre sur pied les ressources E41 correspondent étroitement aux phases du modèle du cycle de l’innovation. La rétroaction des enseignants a confirmé l’utilité de E41 pour les compétences et les mentalités en innovation chez les étudiants. L’analyse des données du sondage a également fait ressortir la présence, et le besoin, d’un leadership solide, d’un appui souple, de mentalités itératives et de structures organisationnelles organiques. Mots clés : innovation, éducation, curriculum, interdisciplinaire